2002
DOI: 10.1530/rep.0.1230333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control of luteal secretion of progesterone

Abstract: The control of progesterone synthesis in the corpus luteum is more complex than is shown in the general pathway for biosynthesis of progesterone in a luteal cell ( Fig. 1) because there are at least two morphologically and biochemically distinct steroidogenic types of cell in the corpus luteum of cattle and sheep and most other mammalian species (Niswender and Nett, 1994; Fig. 2). In ewes, small luteal cells are 12-20 µm in diameter, thought to be of follicular thecal cell origin, contain receptors for LH, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
11

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 8 publications
1
103
0
11
Order By: Relevance
“…However, because fish oil was not the dietary lipid supplement in that instance, the recent reports by Wonnacott et al (2010) and Hughes et al (2011) are more pertinent to the current study. Among their findings, Hughes et al (2011) indicated that n-3 PUFAs specifically enhance progesterone synthesis by thecal cells of ovine follicles and that this is associated with increased StAR transcript expression, notable because the translated steroidogenic acute regulatory protein is an important facilitator of cholesterol transport to mitochondrial membranes, the rate-limiting step in progesterone biosynthesis (Stocco and Clark, 1996;Niswender, 2002). Further reassurance that fish oil was unlikely to have compromised luteal-phase progesterone production in the present study derives from the fact that n-3 fatty acids in fish oil appear able to confer an additional benefit of reducing the synthesis of the uterine antiluteolytic agent, PGF 2α , even when luteal-phase progesterone concentrations are low (Wamsley et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, because fish oil was not the dietary lipid supplement in that instance, the recent reports by Wonnacott et al (2010) and Hughes et al (2011) are more pertinent to the current study. Among their findings, Hughes et al (2011) indicated that n-3 PUFAs specifically enhance progesterone synthesis by thecal cells of ovine follicles and that this is associated with increased StAR transcript expression, notable because the translated steroidogenic acute regulatory protein is an important facilitator of cholesterol transport to mitochondrial membranes, the rate-limiting step in progesterone biosynthesis (Stocco and Clark, 1996;Niswender, 2002). Further reassurance that fish oil was unlikely to have compromised luteal-phase progesterone production in the present study derives from the fact that n-3 fatty acids in fish oil appear able to confer an additional benefit of reducing the synthesis of the uterine antiluteolytic agent, PGF 2α , even when luteal-phase progesterone concentrations are low (Wamsley et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The CL is a primary source of P 4 , a prerequisite hormone required for the maintenance of pregnancy (Niswender, 2002). Inhibition of luteal P 4 production is a key feature of luteolysis occurring in cyclic non-pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…An association between activation of the PKC- [Ca 2+ ] i system and luteal secretion of P 4 was observed in pigs (Ciereszko et al, 1998) and ruminants (Niswender, 2002). Oxytocin produced locally in the porcine CL appears to act as a para/autocrine modulator of luteal steroidogenesis (Einspanier et al, 1991;Pitzel et al, 1993bPitzel et al, , 1993c, but no data are available concerning OT signalling in porcine luteal cells.…”
Section: (Received 2 January 2008; Accepted 22 May 2008)mentioning
confidence: 99%
“…Em bovinos, estudos com CL demonstraram a presença de receptores PTGFR, em células endoteliais e células luteais pequenas, em quantidade pouco significativa, ao contrário das células luteais grandes, nas quais esses receptores são abundantes (SAKAMOTO et al, 1994). Já em ovelhas, o PTGFR foi identificado somente nas células luteais grandes, enquanto que as células luteais pequenas não respondem à ação da PGF2 (NISWENDER, 2002). A resposta luteal à PGF2 é a diminuição da síntese de progesterona, pela diminuição da captação e do transporte de colesterol celular e pela diminuição da expressão de enzimas esteroidogênicas (NISWENDER et al, 2000).…”
Section: Receptores De Prostaglandinasunclassified